ARAH BARU PENDIDIKAN ISLAM: PENDIDIKAN KARAKTER, SPIRITUALITAS, DAN PSIKOTERAPI ISLAM - Nurjasmi Nurjasmi; Khairunnas Rajab (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This research aims to explore a new direction of Islamic Education that integrates three main pillars: character education, spirituality strengthening, and Islamic psychotherapy approaches. In the context of the modern era influenced by globalization, technology, and moral crises, Islamic education is no longer enough to focus only on the transfer of cognitive knowledge, but must become a holistic transformation medium that forms a complete Muslim personality (insan kamil). Through a literature study with a qualitative approach, this article analyzes key concepts such as internalization of values, teacher examples, religious habits, integrative curriculum, and Islamic psychotherapy methods such as takhalli, tahalli, and tajalli. The results of the study show that the integration of these three aspects can strengthen the spiritual mental resilience of students, form noble characters, and answer psychosocial challenges in the digital era. The recommendations put forward include improving the competence of Islamic Religious Education teachers, developing a value-based curriculum, and implementing a psychospiritual approach in educational practice.